2014
DOI: 10.1007/s11552-013-9592-8
|View full text |Cite
|
Sign up to set email alerts
|

A Role Delineation Study of Hand Surgery in the USA: Assessing Variations in Fellowship Training and Clinical Practice

Abstract: Background We examined the fellowship experience of hand surgeons in the USA to identify gaps and variations in exposure to essential skills and knowledge during hand fellowship. Methods We conducted a web-based survey of the entire American Society for Surgery of the Hand and American Association for Hand Surgery membership. We inquired about the level of exposure received to 170 knowledge topics and procedures during fellowship. We used factor analysis to group the knowledge topics and procedures into 79 sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Previous studies showed that trainees in orthopedic hand fellowships have more experience with bone and joint surgery, arthroscopy, and issues proximal to the wrist, whereas plastic surgery hand fellowships have more exposure to soft tissue reconstruction, microsurgery, and congenital hand issues. 1 , 2 Among all fellowships, trainees experience considerable variability in exposure to pathology proximal to the forearm, shoulder arthroscopy, and congenital cases. 2 , 3 A survey of hand surgery fellowship directors confirms this heterogeneity.…”
mentioning
confidence: 99%
“…Previous studies showed that trainees in orthopedic hand fellowships have more experience with bone and joint surgery, arthroscopy, and issues proximal to the wrist, whereas plastic surgery hand fellowships have more exposure to soft tissue reconstruction, microsurgery, and congenital hand issues. 1 , 2 Among all fellowships, trainees experience considerable variability in exposure to pathology proximal to the forearm, shoulder arthroscopy, and congenital cases. 2 , 3 A survey of hand surgery fellowship directors confirms this heterogeneity.…”
mentioning
confidence: 99%
“…[5][6][7][8] Additionally, there is great diversity among fellowships with respect to exposure to faculty of different training backgrounds and types of experiences regardless of fellowship accreditation. 6,9 J Hand Microsurg Residency Training and Hand Practice Patterns Drinane et al…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] Additionally, there is great diversity among fellowships with respect to exposure to faculty of different training backgrounds and types of experiences regardless of fellowship accreditation. 6,9 Prior studies examining the role of residency training and hand surgery practice patterns have primarily consisted of surveys 9,10 and examined the differences in Certification in the Subspecialty of Surgery of the Hand (CAQ) applicants case logs based on type of residency training. 5 There is no prior study examining the role that training background has on practice patterns using objective data after the stringent requirements for case collection and subsequent board certification has passed.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] There is significant variability in training programs, with orthopedic hand fellowships emphasizing bone and joint surgery, arthroscopy, and including shoulder and elbow procedures, while plastic surgery hand fellowships emphasize microsurgery, soft tissue injury, hand fracture fixation, and wound coverage, although some orthopedic programs also perform microsurgery with replantation and large reconstructive procedures. 10,11 Due to the broad scope of cases in hand surgery, training programs integrating both orthopedic surgery and plastic surgery disciplines are becoming increasingly common. 11,12 In addition, many health care systems do not require additional fellowship training in hand surgery or achievement of certificate of added qualification (CAQ) to provide hand surgery treatments.…”
Section: Introductionmentioning
confidence: 99%